Patterns of Relationship between Islamic Values and Social Science Issues in Thematic Books for Grade IV Elementary School - Rahmi, Rina (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
The purpose of this research is to study and analyze the regularity of the relationship between Islamic values and social science subjects/materials contained in the thematic book theme 3 "Caring for Living Things" published by the Ministry of Education and Culture revised edition 2017, using Ian G. Barbour's theory which formulates 4 typologies namely conflict, independence, dialogue, and integration. This research is a type of qualitative research using library research method or content analysis. The data collection technique uses documentation techniques to collect information, which is then analyzed to determine whether the data obtained is relevant and valid. Data analysis uses some equipment (pencils, pens, and note paper), bibliographic work, preparing and determining time, reading, and then concluding. The object of this research is the thematic book theme 3 revision 2017 published by the Ministry of Education and Culture grade IV SD / MI. This study found that the relationship between Islamic values and social issues in thematic thematic books includes 3 of the 4 typologies proposed by Barbour namely: a) independent, c) dialog, and d) integration. There is no conflict between social science materials and Islamic values (religion) because both can be united by finding common points between social science and Islamic values. This is done based on references to Quranic verses.In this case, the social science issues in the textbook are integrated with Islamic values by tracing the verses of the Quran.